Sistema de controle estratégico e capacidades dinâmicas: um estudo na Itaipu Binacional - Tavares, Ronaldo (2021)
Several papers have linked different organizational outcomes as precedents to Dynamic Capabilities (DC), with we highlight on entrepreneurship, environmental dynamism, resources, knowledge management, organizational learning and managerial controls. Sporadically, studies have been conducted that relate the Levers of Strategic Control Framework proposed by Simons (1995) to the micro-foundations of Dynamic Capabilities proposed by Teece (2007). This paper aims to evaluate how the Levers of Strategic Control Framework is related to the microfoundations of Dynamic Capabilities at Itaipu Binacional. The case that was investigated is a Brazilian and Paraguayan hydroelectric power plant. Data were collected through a survey among the population of employees of the company's own staff and forward through confirmatory composite analysis and the structural equations modeling, considering the method of partial least squares; to test the central hypothesis that the use of Control Levers is positively associated and influences the presence of Dynamic Capabilities. The results obtained validate the central hypothesis, as well one of the complementary hypotheses, that Interactive System is positively associated and influences the presence of the capability to Sense Opportunities.